PENGARUH CASH TURNOVER, RECEIVABLE TURNOVER, DAN INVENTORY TURNOVER TERHADAP RETURN ON ASSET PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Irnanda Khabilah Umayta; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe purpose of this research to determine the influence of Cash Turnover, Receivable Turnover and Inventory Turnover towards Return On Asset of Property company for the period 2015-2017. The data used in this study is secondary data. The population used is Property and real estate company at BEI for the period 2015-2017. The sampling technique was done by purposing sampling method. The sample of this research is 30 companies. Data analysis was done by using multiple linier regression method. The result of this study indicate that (1) Cash Turnover has a significant positive effect on ROA, with a significance level of 0,875 > 0,05. (2) Receivable Turnover has a significant positive effect on ROA, with a significance level of 0,197 > 0,05. (3) Inventory Turnover has a significant positive effect on ROA, with a significance level of  0,392 > 0,05.Keywords: Cash Turnover, Receivable Turnover, Inventory Turnover and Return On Asset.